2006
DOI: 10.1074/jbc.m603698200
|View full text |Cite
|
Sign up to set email alerts
|

The Heme Transfer from the Soluble HasA Hemophore to Its Membrane-bound Receptor HasR Is Driven by Protein-Protein Interaction from a High to a Lower Affinity Binding Site

Abstract: HasA is an extracellular heme binding protein, and HasR is an outer membrane receptor protein from Serratia marcescens. They are the initial partners of a heme internalization system allowing S. marcescens to scavenge heme at very low concentrations due to the very high affinity of HasA for heme (K a ‫؍‬ 5,3 ؋ 10 10 M ؊1 ). Heme is then transferred to HasR, which has a lower affinity for heme. The mechanism of the heme transfer between HasA and HasR is largely unknown. HasR has been overexpressed and purified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
102
3
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(120 citation statements)
references
References 34 publications
(42 reference statements)
13
102
3
2
Order By: Relevance
“…3 However, incubation of E. coli cultures expressing HasR or PhuR with either heme or hemoglobin increased the heme content of the purified receptor. This is in contrast to previous reports where the purified S. marcescens HasR receptor was reported to strip heme from holo-HasA (21). Additionally, the ShuA receptor of S. dysenteriae was shown to accept heme from methemoglobin in lipid bicelles but not free heme (23) and the recently characterized N. meningitidis HmbR receptor was unable to be reconstituted with heme or hemoglobin following purification (26).…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…3 However, incubation of E. coli cultures expressing HasR or PhuR with either heme or hemoglobin increased the heme content of the purified receptor. This is in contrast to previous reports where the purified S. marcescens HasR receptor was reported to strip heme from holo-HasA (21). Additionally, the ShuA receptor of S. dysenteriae was shown to accept heme from methemoglobin in lipid bicelles but not free heme (23) and the recently characterized N. meningitidis HmbR receptor was unable to be reconstituted with heme or hemoglobin following purification (26).…”
Section: Discussioncontrasting
confidence: 92%
“…Recent kinetic and spectroscopic studies of the P. aeruginosa HasA protein have shown that heme acquisition from methemoglobin is relatively passive, occurring at a rate similar to that of heme dissociation (20). Therefore, the capture of dissociated heme by HasA and its reported nanomolar binding affinity to the HasR receptor, would allow the bacteria to access a wider range of heme concentrations within the host environment (21). Sequence alignment of all TonB-dependent OM heme receptors in combination with site-directed mutagenesis of the Yersinia entercolitica HemR, identified the highly conserved His residues located in the predicted N-terminal plug and conserved FRAP/PNPNL loop as being required for heme uptake (22).…”
mentioning
confidence: 99%
“…This mechanism is similar to that of hemin and heme transfer from streptococcal Shp to apo-HtsA (14). Protein interaction also is critical for hemin transfer from Serratia marcescens hemophore HasA to HasA receptor HasR (1). The mechanism of activated heme transfer may apply in general to all direct heme transfers in bacterial heme transport systems.…”
Section: Kinetic Parametermentioning
confidence: 81%
“…UV-visible absorbance spectroscopy was used to check sample integrity before and after the rR spectra were recorded. The spectra were recorded at ambient temperature as previously described (23). The spectra were calibrated using the Raman bands of toluene and dimethylformamide.…”
Section: Methodsmentioning
confidence: 99%
“…The experiments were carried out on protein samples with concentration ranging from 0.1 to 0.5 mM in 50 mM sodium acetate buffer, pH 5.5, 50 mM phosphate buffer, pH 7, and 50 mM Tricine, pH 9. Spin quantitations of the low and high spin heme signals were performed in nonsaturating conditions as previously described (23).…”
Section: Methodsmentioning
confidence: 99%